Medical expulsion therapy for ureteric calculus – possible! - Ramesh, A.; Karthick, P.; Kumar, R. Shiva (International Surgery Journal, 2016)
Background: Objective of the study was to compare the efficacy of combination of Tamsulosin and Deflazacort with that of analgesics alone, in medical expulsive therapy (MET) of solitary ureteric calculus ≤1 cm. Methods: A prospective randomized study was conducted in 100 patients of Chennai medical college hospital & Research centre from General Surgery and Urology Out-Patient Department (OPD). Patients with symptomatic, solitary ureteric calculus ≤10mm were included. Patients with solitary functioning kidney, history of prior urinary surgery or endoscopic treatment, any associated complication or any contraindications of steroid usage were excluded. Patients were divided into two groups: Group I received Diclofenac 50mg on demand and Group II received Tamsulosin with Deflazacort (0.4mg+30mg respectively) along with analgesic for a maximum of 2weeks. Results: Calculus expulsion was significantly higher in Group II (84%) compared to that in Group I (60%) (p=0.008). Higher expulsion rate in Group II was primarily seen in the patients with a calculus size of ≥5 mm. There was no difference in stone expulsion rates in patients with stones less than 5mm. 19 patients in group II were free of pain compared to 7 patients in group I (p= 0.006). Group II patients had significant reduction in expulsion time and analgesic requirement. Conclusions: MET with alpha blocker and steroid combination is effective, safe and economical treatment for symptomatic urolithiasis and scores over treatment with analgesics, alone. This combination can be used as initial therapy for stone expulsion and symptomatic relief, thereby avoiding or delaying surgical intervention in selected patients.